Exercise and Alcohol Consumption: What We Know, What We Need to Know, and Why it is Important - Leasure, J. Leigh; Neighbors, Clayton; Henderson, Craig E.; Young, Chelsie M. (Frontiers in Psychiatry, 2015)
Exercise provides a wealth of benefits to brain and body, and is regarded as a protective factor against disease. Protective factors tend to cluster together - that is, people who engage in one healthy behavior, such as exercise, also engage in other healthy behaviors, such as maintaining a nutritious diet and getting sufficient sleep. In contrast to exercise, alcohol consumption is not typically regarded as a health-promoting behavior, although moderate intake has been associated with a lower risk of cardiovascular disease. Surprisingly, several large, population-based studies have shown a positive association between physical activity and alcohol intake. The present review focuses on what is known about this relationship, including potential neural bases as well as moderating factors, and discusses important directions for further study, such as a more thorough characterization of people who both drink and exercise. We focus on ramifications for intervening with people that have alcohol use disorders (AUD), as exercise has been assessed as both a treatment and preventive measure, with mixed results. We believe that, in order for such interventions to be effective, clinical trials must distinguish treatment-seeking populations from non, as well as ensure that the use of exercise as a tool to decrease alcohol consumption is made explicit. We posit that a better understanding of the relationship between physical activity and alcohol intake will maximize intervention efforts by informing the design of clinical trials and research-driven prevention strategies, as well as enable individuals to make educated decisions about their health behaviors.